Languages of Power and Belongings: A Case Study of a Papuan Student’s Struggle for Identity in a Multilingual University - Satriyo, Aria Maulana; Riza Ady Sampurna; Roosi Rusmawati (Linguistik Indonesia, 2025)
This research explores how the variation in language, including practices like code-switching and shifts in dialect, influences the formation of social identities within academic communities characterized by multilingualism. The study focuses on a student from Papua at Universitas Kristen Satya Wacana (UKSW), where language plays a critical role in expressing cultural connections, managing interpersonal dynamics, and navigating power structures. By conducting a qualitative research through interviews and participant observation, the study investigates how the student utilizes his diverse linguistic skills to negotiate his identities and either connect with or distance himself from different social groups. The findings highlight the dual role of language in both including and excluding individuals, which mirrors broader sociocultural power structures. Specifically, the Papuan student employs language strategically to assert his regional identity while also adapting to national and global standards. This research advances our understanding of language variation as a significant sociolinguistic phenomenon and underscores its intricate relationship with identity construction in academic environments. The results offer valuable insights for both the field of sociolinguistics and for understanding how marginalized linguistic communities navigate the challenges of social and academic integration.